Life cycle cost for construction projects. Input lecture for AAR 7453 Professional Practice 1, (Master of Architecture Programme) - Ayob, Mohd Fairullazi (2019)
Input Lecture for AAR 7453 Professional Practice 1, (Master of Architecture Programme), Department of Architecture, Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia (15th October 2019)